Democratic silence: two forms of domination in the social contract tradition. Issue 3 (16th April 2021) - Rollo, Toby
ABSTRACT: The social contract tradition has been critiqued for harboring 'domination contracts' that exclude women, people of color, people with disabilities, and others from political life. In this article, I build on these critical analyses to argue that the liberal ideal of the reasoning and speaking citizen entails the anti-democratic disqualification of 'silent' citizens such as young children and many peoples with intellectual disabilities. The liberal veneration of voice and the corollary vilification of silence represent the internal logic of all domination contracts, since it is by comparison to silent children and peoples with disabilities that groups such as women and people of color are viewed as justifiably excluded. I identify two distinct but interacting forms of liberal disqualification: (1) contingent domination contracts, which can be potentially disputed and temporarily resolved by proving a group's fulfilment of the qualifications of speech and reason; and (2) structural domination contracts, which cannot be resolved for 'silent' citizens. Moreover, any viable challenge to a contingent domination contract must centre on the democratic inclusion of silent citizens, which itself will require the reconceptualization and redesign of political processes, as well as workplaces, economies, and other social institutions.